Backscattered electron emission after proton impact on gold nanoparticles with and without polymer shell coating. (12th June 2019) - Hespeels, F; Heuskin, A C; Tabarrant, T; Scifoni, E; Kraemer, M; Chêne, G; Strivay, D; Lucas, S
Abstract: This work aims at measuring experimentally proton induced secondary electron energy spectra after interaction with gold nano particles (GNPs) and polymer-coated GNPs. Backscattered electron energy spectra were collected over a 0 to 1000 eV energy range using a retarding field analyzer (RFA). This paper presents the spectra obtained for proton beam energies of 0.5 and 2 MeV and diameter 2.5 and 3.8 nm GNPs. The spectra were also measured for 3.8 nm GNPs after 5 and 10 MeV proton irradiations. GNPs were deposited on a 100 nm carbon film. Each experimental spectrum was compared with dedicated simulations based on existing numerical models used in the TRAX and Geant4 Monte Carlo codes. For 100 nm carbon target, good agreement between experimental, TRAX and Geant4 simulation results can be observed. For 3.8 nm GNPs, the TRAX simulations reproduce with good agreement the electron energy spectra produced after 0.5, 2, 5 and 10 MeV proton irradiations, while Geant4 spectra display a lower secondary electron yield at low energy (<600 eV) for all the studied energies. This underestimation can mostly be explained by the 790 eV threshold applied in the condensed history model used by Geant4 which impacts the secondary electron energy distribution. Results obtained for carbon and gold targets highlight the impact of the secondary electron production threshold for proton ionization process considered in condensed history models. The experimental results demonstrate that the single interaction approach used in TRAX is adapted to reproduce secondary electron emission from GNPs. On the other hand, the standard electron generation threshold implement in G4BetheBlochModel and G4BraggModel condensed-history models used in Geant4 is not adapted to reproduce low energy electron emission in gold targets. Finally, the results highlight that the GNP coating leads to a decrease of the electron yield and mostly affects low energy electrons (<500 eV) emitted from GNPs.